The Impact of Professional Skills on the Quality of Auditing Performance: A Field Study in Audit Offices and Firms in the Republic of Yemen - Al-Sorihi, Sultan Ali Ahmed; Shboor, Afnan Abdusalam Hasan (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to investigate the impact of professional skills on the quality of audit performance from the perspective of certified public accountants in audit offices and firms in the Republic of Yemen. To achieve this objective, a questionnaire was used to collect data from a purposive sample of (190) certified accountants working in auditing offices and firms in Yemen. A total of 184 valid questionnaires were retrieved for statistical analysis. The study adopted a descriptive analytical approach and utilized multiple regression analysis. The results revealed a positive impact of professional skills (intellectual skills, personal skills, and organizational and administrative skills) on the quality of auditing performance. However, no significant impact was found for two dimensions of professional skills (technical and practical skills, and communication skills) on the quality of auditing performance. The study results also showed that the sub-dimension most strongly correlated with audit quality performance was client relationships, followed by audit engagement execution, documentation and follow-up, and leadership responsibility. Based on these findings, the study recommends that audit firms should establish a dedicated department responsible for audit quality control, with leadership demonstrating willingness to provide adequate resources for quality control development. This would contribute to enhancing their technical and cognitive skills, enabling them to perform their duties and make sound decisions in the audit process.